Reconstruction of Kurdish National Identity in the Approved Textbook for Studying Social Subjects of the Second Grade of Secondary School in the Kurdistan Region - Khorshid, Aram Anwar; Hussin, Rekawt Mirowis (Sulaimani Journal for Humanities, 2025)
The aim of this study is to analyze the reflection of Kurdish national identity in the decision-making to study social subjects in primary schools in the Kurdistan Region. In this study, the descriptive method (content analysis) has been used. The research community consists of the decided textbooks of social subjects in all three grades of fourth, fifth and sixth primary cycle two, the academic year 2024-2025, after a careful and in-depth reading of the social issues decisions in the second cycle, the researchers present several signs and historical and geographical characteristics of national identity mentioned in these decisions. The research concluded that the curriculum of the second cycle of primary schools, the decisions on social issues with several important and specific signs indicate the identity of the Kurdish nation. Historically, these symbols include the Kurdish calendar, Newroz feast, revolutions and uprisings, emirates, the Kurdistan Republic, famous personalities, ancient nations, Anfal and chemical attack on Halabja, Kurdistan's monuments and caves, museums, etc. However, geographically, the signs of national identity include the dialect of the Kurdistan Region, the geographical location of the Kurdistan Region, the ancient cities of the Kurdistan Region, the territory of the Kurdistan Region, natural plants, water resources, industrial products, Minerals and Industry in the Kurdistan Region...etc. Each of these signs has a significant impact on the identity of the Kurdish nation among students. The historical dimension of social issues has given more importance to national identity than the geographical dimension. Famous personalities have also played the lion's share in deciding social issues. They are the main reasons for introducing the Kurdish nation to students. These personalities include political, religious, cultural and literary figures such as poets. The fourth grade social issues decision book contains the least signs of ethnic identity, compared to the fifth and sixth grades. The researchers make several recommendations to the stakeholders to seriously revise the textbooks of grade four social subjects that contain the least signs of ethnic identity. Also, changes in the curriculum and consolidation and more attention to national holidays such as (uprising, Anfal, chemical attack on Halabja, Flag Day, Kurdish clothes day and Kurdish New Year) and introduce students to be aware of the history of our nation.
Keywords: Identity; national identity; study Decisionmaking; social issues